Global aging and fiscal policy with international labor mobility: a political economy perspective - Mehmet Serkan Tosun (Institute for the Study of Labor (IZA), 2009)
This paper uses an overlapping generations model with international labor mobility and a politically responsive fiscal policy to examine aging in developed and developing regions. Migrant workers change the political structure composed of young and elderly voters in both labor-receiving and labor-sending countries. Numerical simulations show that the developed region benefits more from international labor mobility through the contribution of migrant workers as laborers, savers, and voters. The developing region experiences significant growth in all specifications but benefit more under international capital mobility. Restricting political participation of migrant workers in the developed region produces inferior growth results.
urn:nbn:de:101:1-20090605232
Keywords: E62; F21; F22; F43; H30; J10; 330; Population aging; overlapping generations; endogenous fiscal policy; international labor mobility; international capital mobility; Alternde Bevölkerung; Overlapping Generations; Finanzpolitik; Internationale Arbeitsmobilität; Kapitalmobilität; Theorie; Welt; Entwicklungsländer